PROVERBS AND SAYINGS AS COMMUNICATIVE PHRASEOLOGICAL UNITS (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Proverbs and sayings serve as concise linguistic expressions encapsulating cultural wisdom, moral lessons, and societal values. This article explores their communicative role, emphasizing their educational significance, linguistic roots, and global variations. Delving into cultural nuances and hidden meanings, it sheds light on their adaptability in the digital age, influence on language learning, and anthropological insights into human behavior. The continued resonance of these communicative phraseological units highlights their role in perpetuating oral tradition and preserving cultural heritage.